HGG-44. STRESSED TO DEATH: EGFRvIII EXPRESSION RENDERS GLIOBLASTOMA CELLS MORE SENSITIVE TO ER STRESS INDUCING CHEMOTHERAPEUTICS. Issue 2 (22nd June 2018) - Graham, Regina; Kostenko, Katrina; Torrens, Ingrid; De Cordoba, Nicolas; Freire, Melanie; Camile, Fedeline; Vanni, Steven
Abstract: Epidermal growth factor receptor (EGFR) is often overexpressed and/or mutated cancer. The most common mutation is EGFRvIII and has been found to correlate with tumor aggressiveness and poor outcome. In glioblastoma (GBM) expression of EGFRvIII is linked to cell-signaling pathways required for increased cell proliferation, cancer stem-cell self-renewal and tumor invasiveness. Although the mechanisms by which EGFRvIII confers increased tumorigenecity are not fully understood, recent evidence suggests that endoplasmic reticulum (ER) proteostasis plays a key role in tumor aggressiveness and resistance to therapy. Here we sought to determine the role of EGFRvIII expression on GBM ER stressed-induced cell death. U87 and U87 EGFRviii expressing cells were exposed to the following ER stress inducers: 2-deoxy-D-glucose (2-DG, 0.5mM), velcade (10nM), tunicamycin (0.05ug/ml) or withaferin A (WA, 1uM) and viability determined by MTS assay. EGFRvIII expressing cells were approximately 2-fold more sensitive to these ER stress inducers; viability of 2-DG, velcade, tunicamycin and WA treated U87 cells was 71.1 + 3.6%, 92.5 + 2.7%, 55.3 + 3.8% and 77.2 + 6%, respectfully, verses 24.5 + 1.1%, 46.8 + 3, 22.7 + 2.1% and 19.5%, respectfully in EGFRvIII expressing U87 cells. Western blot analysis demonstrated higher levels of ER stress markers, GRP78 and CHOP. Effective mediation of ER stress is necessary for cancer cells to maintain uncontrolled growth and enhanced protein production. However this dependence provides a target for treatment intervention. Our data suggests that patients whose tumors express EGFRvIII may benefit from ER stress inducing chemotherapies.